2006
DOI: 10.1089/aid.2006.22.1186
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HIV Type 1 Diversity in Pregnant Women from Four Latin American and Caribbean Countries

Abstract: Worldwide, the distribution of HIV-1 subtypes and intersubtype recombinants is not homogeneous. In Latin America and the Caribbean, HIV-1 subtype B predominates. However, in the south of Brazil and in countries of the Southern cone (Argentina, Chile, Paraguay, and Uruguay) there is a different distribution of viral subtypes and intersubtype recombinants. The aim of this work was to analyze HIV-1 diversity in a cohort of pregnant women (with primarily heterosexual acquisition of the infection) who were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…However, several studies on molecular characterization have shown that HIV-1 epidemics in South America are constituted not only by subtype B strains but also by subtype F strains, as well as recombinants between both subtype B and F. [7][8][9][10][11][12][13][14][15][16][17][18] In particular, the prevalence of BF recombinants is significantly higher than that observed for pure subtype F strains, reaching a prevalence similar to subtype B strains in some regions. 14 Considering the genetic distance between subtypes B and F, the presence of the BF recombinants in South America can only be explained by a second introduction of HIV-1 into the American Continent, independent of what occurred in the Caribbean/U.S.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies on molecular characterization have shown that HIV-1 epidemics in South America are constituted not only by subtype B strains but also by subtype F strains, as well as recombinants between both subtype B and F. [7][8][9][10][11][12][13][14][15][16][17][18] In particular, the prevalence of BF recombinants is significantly higher than that observed for pure subtype F strains, reaching a prevalence similar to subtype B strains in some regions. 14 Considering the genetic distance between subtypes B and F, the presence of the BF recombinants in South America can only be explained by a second introduction of HIV-1 into the American Continent, independent of what occurred in the Caribbean/U.S.…”
Section: Introductionmentioning
confidence: 99%
“…These reports indicate that near 50% of the HIVinfected people living in Argentina are infected either with the circulating recombinant form CRF12_BF or other BF recombinant forms related to CRF12_BF. Moreover, in other South American countries, such as Brazil and Uruguay, high prevalence of F subtype and BF recombinant variants are also found (16,32,34). These findings provide an adequate scenario to fill the gap concerning fine mapping of CTL responses in nonclade B-and C-infected patients.…”
mentioning
confidence: 99%
“…To date, most reports aimed at studying CTL responses are focused on HIV clade Band C-infected patients. In Argentina, epidemiological studies revealed that early predominance of B subtype has been overshadowed by the emergence of BF recombinants (16,23,32,33,53). These reports indicate that near 50% of the HIVinfected people living in Argentina are infected either with the circulating recombinant form CRF12_BF or other BF recombinant forms related to CRF12_BF.…”
mentioning
confidence: 99%
“…First, strains with very similar genetic backgrounds (like subtype C and CRF31_BC) displayed very different spreading rates. Second, the prevalence of subtype C and CRF31_BC in regions that bordered southern Brazil, such as the southeast Brazilian region, [33][34][35] Argentina, 36,37 Paraguay, 38 and Uruguay, 39 remains very low (<6%), with no evidence of a rapidly increasing trend through time as has happened in the southern Brazilian region. We suggest that variations in the growth rate of HIV-1 Brazilian variants more likely reflect differences in the transmissions networks that characterized the initial spread of the subtypes rather than differences in intrinsic infectivity, although no clear relationship between risk factors for HIV-1 transmission and strain distribution have been established to date in Brazil.…”
mentioning
confidence: 99%